Conductive paste and method for producing electronic component using the same
By adding components such as dicarboxylic acid dispersants to the conductive paste, the viscosity adjustment problem in gravure printing is solved, the formation of a homogeneous coating film and efficient printing are achieved, and the quality and productivity of electronic components are improved.
Patent Information
- Application Number
- CN202080067677.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-09-25
- Filing Date
- 2020-09-04
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2040-09-04
AI Technical Summary
The viscosity adjustment of the existing conductive paste during gravure printing is difficult to take into account the homogeneity and surface smoothness of the coating film, resulting in the deformation of the laminated structure and poor short circuit.
Use conductive paste containing conductive powder, dielectric powder, binder resin, solvent and dicarboxylic acid-based dispersant to adjust its viscosity and dispersant structure to ensure low viscosity, homogeneity and smooth surface in gravure printing coating.
The high-efficiency printing and homogeneous coating film formation of conductive pastes with low viscosity in gravure printing are achieved, reducing the occurrence of deformation of stacked structures and short circuit failures, and improving the quality and productivity of electronic components.
Smart Images

Figure CN114503220B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a conductive paste and a method for producing an electronic component using the same.
[0002] It should be noted that the present application claims priority based on Japanese Patent Application No. 2019-174262 filed on September 25, 2019, the entire contents of which are incorporated into this specification as a reference. Background Art
[0003] In the manufacture of electronic components, a method of applying a conductive paste to a substrate to form a coating and firing it to form an electrode layer is widely used. For example, in an example of a method for manufacturing a multilayer ceramic capacitor (MLCC), first, a plurality of unfired dielectric green sheets containing dielectric powder, etc. are prepared. Then, a conductive paste containing conductive powder and a resin binder, etc. is applied to the dielectric green sheet and dried to form a coating. Then, a plurality of dielectric green sheets with coatings are stacked and pressed together by applying pressure in the stacking direction. Then, after cutting it into a specified size, it is fired so that it is sintered as a whole. Then, external electrodes are formed on the two end faces of the fired composite. In this way, an MLCC having the following structure is manufactured: it alternately stacks a plurality of dielectric layers formed of dielectric powder and internal electrode layers formed of a fired body of conductive paste (for example, refer to patent documents 1 and 2).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2014-122368
[0007] Patent Document 2: Japanese Patent Application Publication No. 2012-174797 Summary of the invention
[0008] However, in recent years, as various electronic devices have become more advanced in performance, the electronic components installed in the electronic devices are also required to be thinner, smaller, and more dense. For example, for MLCC, it is required to increase the number of layers by reducing the thickness of one layer of the internal electrode layer, thereby miniaturizing the volume of the MLCC and increasing the electrostatic capacitance.
[0009] Based on such a situation, when the conductive paste for forming the internal electrode layer is applied, the gravure printing method is gradually used to replace the screen printing method. Since the gravure printing method has a faster printing speed than the screen printing method, it has excellent productivity and can form a thin film with stable quality. As mentioned above, due to the fast printing speed of gravure printing, if the viscosity of the conductive paste is adjusted to the same degree as that of screen printing, the surface of the coating is sometimes rough and the concave and convex becomes larger. This will cause deformation of the stacked structure and become the cause of adverse conditions such as short circuit failure. Therefore, the conductive paste for gravure printing needs to be adjusted to a lower viscosity than the conductive paste for screen printing. However, in the case of containing inorganic powders with different particle sizes and specific gravities, such as conductive powders and dielectric powders, the inorganic powders in the conductive paste are easily separated and it is difficult to form a homogeneous coating.
[0010] The present invention has been made in view of the above-mentioned circumstances, and an object of the present invention is to provide a conductive paste which has low viscosity, is excellent in gravure printability, and can form a homogeneous coating film, and a method for producing an electronic component using the same.
[0011] The present invention provides a conductive paste for gravure printing, comprising: (A) conductive powder, (B) dielectric powder, (C) binder resin, (D) solvent and (E) dispersant. The dispersant (E) comprises a dicarboxylic acid dispersant having a structural part represented by the following formula (1).
[0012]
[0013] (Wherein, A in formula (1) 1 , A 2 Each independently is hydrogen, alkali metal or alkaline earth metal. ). At 25° C., the conductive paste is subjected to a shearing speed of 40 s -1 Viscosity V 40 Less than 5Pa·s.
[0014] In the technology disclosed herein, the above-mentioned dispersant is included and the viscosity V is adjusted to the above-mentioned 40 , thus realizing the conductive paste of the character suitable for gravure printing.Thus, it is not easy to produce printing collapse etc., and a coating film can be formed quickly and stably on substrate.In addition, for example, compared with the situation of using other anionic dispersants (for example, the dispersant of monocarboxylic acid system, the dispersant of dicarboxylic acid system without the structural part of above-mentioned formula (1), the dispersant of polycarboxylic acid system, sulfonic acid system dispersant, phosphoric acid system dispersant etc.), the dispersant of amine system etc., the dispersibility of conductive powder and dielectric powder is good, and a coating film with smooth surface can be formed.
[0015] In a preferred embodiment of the conductive paste disclosed herein, the dispersant (E) is a compound represented by the following formula (2).
[0016]
[0017] (Wherein, A in formula (2) 1 , A 2 Each is independently hydrogen, an alkali metal or an alkaline earth metal, and R is a linear or branched, saturated or unsaturated aliphatic group having 3 to 30 carbon atoms. ).
[0018] In a preferred embodiment of the conductive paste disclosed herein, the conductive paste is subjected to a shearing speed of 4 s -1 The viscosity V4 below is relative to the above viscosity V 40 The ratio (V4 / V 40 ) is 7 or less. This can improve the printability of the conductive paste.
[0019] In a preferred embodiment of the conductive paste disclosed herein, the ratio (D1 / D2) of the average particle size D1 of the conductive powder (A) to the average particle size D2 of the dielectric powder (B) is 2 or more. In this way, by making the particle sizes of the conductive powder and the dielectric powder greatly different, the dispersibility of the inorganic powder (especially the dielectric powder) in the conductive paste is likely to be significantly reduced. As a result, it is particularly difficult to form a homogeneous coating film. Therefore, the application of the technology disclosed herein exerts a high effect.
[0020] In a preferred embodiment of the conductive paste disclosed herein, the solvent (D) includes a hydrocarbon solvent and a non-hydrocarbon solvent, and the non-hydrocarbon solvent includes a solvent having a boiling point of 230° C. or less and a solubility parameter of 9.9 (cal / cm 3 ) 0.5 The following solvents are used. Thus, the sheet attack phenomenon of the green sheet caused by the solvent can be suppressed at a high level. In addition, the quick drying property of the coating film can be improved, thereby improving productivity.
[0021] In a preferred embodiment of the conductive paste disclosed herein, the non-hydrocarbon solvent includes a solvent having a boiling point of 200° C. or higher and a solubility parameter of 10.0 (cal / cm 3 ) 0.5 The first solvent above; and a boiling point of 220°C or less, and the solubility parameter is 9.5 (cal / cm 3 ) 0.5 The second solvent described below can thereby achieve both the effect of suppressing the sheet erosion phenomenon and the effect of improving quick-drying properties at a higher level.
[0022] It should be noted that in this specification, "Fedors' solubility parameter (Solubility Parameter: SP)" refers to the solubility parameter calculated by the so-called Fedors method described in RF Fedors, Polymer Engineering Science, 14, p147 (1974). In the Fedors method, it is believed that the cohesive energy density and the molar molecular volume depend on the type and number of substituents, and are calculated by the following formula: δ = [ΣE coh / ΣV] 0.5 (Here, Σ Ecoh represents cohesive energy, and ΣV represents molar molecular volume. ) is used to represent the solubility parameter. The solubility parameter is a value inherent to each compound. It should be noted that, hereinafter, the solubility parameter of Fedors is sometimes referred to as "SP value". In addition, the SI unit of SP value is (J / cm 3 ) 0.5 or (MPa) 0.5 In this specification, the conventional (cal / cm 3 ) 0.5 The unit of SP value can be expressed as follows: 1(cal / cm 3 ) 0.5 ≈2.05(J / cm 3 ) 0.5 ≈2.05(MPa) 0.5 ; for conversion.
[0023] In a preferred embodiment of the conductive paste disclosed herein, the solubility parameter of the solvent other than the hydrocarbon system is 9.8 (cal / cm 3 ) 0.5 As a result, the binder resin can be appropriately dissolved and the sheet erosion phenomenon can be better suppressed.
[0024] It should be noted that the solubility parameter δ of the solvent as a whole all It can be expressed by the following formula: all (cal / cm 3 ) 0.5 =Σ〔The intrinsic solubility parameter δ of each solvent (cal / cm 3 ) 0.5 × The mass ratio of each solvent when the whole solvent is taken as the reference (1) is calculated. In other words, first, the intrinsic solubility parameter δ (cal / cm 3 ) 0.5 The product of the mass ratio and the total solubility parameter δ of the solvent is all .
[0025] In a preferred embodiment of the conductive paste disclosed herein, the amount of the dispersant (E) is 0.5% by mass or less when the entire conductive paste is 100% by mass. This allows for an electrode layer having excellent conductivity and density to be appropriately realized.
[0026] In a preferred embodiment of the conductive paste disclosed herein, the binder resin (C) includes a polyvinyl acetal resin having a weight average molecular weight of 200,000 or less. This can improve adhesion to the substrate and suppress uneven distribution of dielectric powder.
[0027] The conductive paste disclosed herein can be used to form an internal electrode layer of a laminated ceramic electronic component. Thus, a smooth film containing inorganic powder uniformly in the coating film can be appropriately formed, and sheet erosion can also be suppressed. As a result, an internal electrode layer that is highly continuous and homogeneous even in a thin film can be formed.
[0028] The present invention also provides a method for producing an electronic component, comprising applying the conductive paste to a substrate and firing the conductive paste. By using the conductive paste, a small-sized, large-capacity, and high-quality MLCC can be appropriately produced. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a cross-sectional view schematically showing the structure of a multilayer ceramic capacitor.
[0030] Figure 2 It is a cross-sectional view schematically showing the structure of an unfired laminated body.
[0031] Figure 3 middle, Figure 3 (A) is the SEM observation image of Comparative Example 3, Figure 3 (B) is a SEM observation image of Comparative Example 9.
[0032] Figure 4 This is a conceptual diagram for explaining a method for calculating a dispersion index.
[0033] Figure 5 middle, Figure 5 (A) is the SEM observation image of Example 5, Figure 5 (B) is a SEM observation image of Comparative Example 11.
[0034] Figure 6 middle, Figure 6 (A) is the cross-sectional profile of the surface roughness of Comparative Example 3, Figure 6 (B) is the cross-sectional profile of the surface roughness of Example 1.
[0035] Figure 7 middle, Figure 7 The TG-DTA measurement diagrams of Example 13, Example 19, and Example 9 are shown.
[0036] Figure 8 middle, Figure 8 (A) is the SEM observation image of Example 19, Figure 8 (B) is the SEM observation image of Example 16. Figure 8 (C) is the SEM observation image of Example 9. DETAILED DESCRIPTION
[0037] The following is a description of a suitable embodiment of the present invention. It should be noted that matters required for the implementation of the present invention (e.g., a method for preparing a conductive paste, a composition of electronic components, etc.) other than matters specifically described in this specification (e.g., the composition of the conductive paste and its properties) can be implemented based on the technical content taught in this specification and the general technical knowledge of those skilled in the art. It should be noted that in this specification, the expression "X to Y (X, Y are arbitrary values)" indicating a numerical range includes the meaning of more than X and less than Y, and the meaning of "preferably greater than X" and "preferably less than Y".
[0038] [Conductive paste for gravure printing]
[0039] The conductive paste disclosed herein comprises: (A) conductive powder, (B) dielectric powder, (C) binder resin, (D) solvent and (E) dispersant. It should be noted that in the following description, (A) conductive powder and (B) dielectric powder are sometimes referred to as "inorganic powder" components, and (C) binder resin, (D) solvent and (E) dispersant are sometimes referred to as "organic components". The conductive paste can be appropriately used for gravure printing.
[0040] It should be noted that in this specification, "coating film" refers to a film-like body (dried product) formed by drying the conductive paste at a temperature lower than the boiling point of the (C) binder resin and / or (E) dispersant, typically 200°C or lower, for example 150°C or lower, preferably 120°C or lower. When the conductive paste is dried at a temperature below the boiling point of the (C) binder resin and / or (E) dispersant, these components will remain in the coating film. The coating film includes the entire unfired (before firing) film-like body.
[0041] In addition, in this specification, the "electrode layer" refers to a sintered body (sintered product) formed by sintering inorganic powders, such as (A) conductive powder and (B) dielectric powder, after organic components in the conductive paste, such as (C) binder resin, (D) solvent, and (E) dispersant, disappear. The electrode layer includes wiring (linear body), wiring pattern, and solid pattern. The components are described in order below.
[0042] (A) Conductive powder
[0043] Conductive powder is a component that imparts conductivity to the electrode layer. The type of conductive powder is not particularly limited, and one or more kinds of conductive powders can be used alone or in combination according to the purpose of the electrode layer. As conductive powder, for example, single substances of base metals such as nickel (Ni), aluminum (Al), copper (Cu), tungsten (W), single substances of precious metals such as gold (Au), silver (Ag), platinum (Pt), palladium (Pd), rhodium (Rh), iridium (Ir), ruthenium (Ru), osmium (Os), and mixtures thereof, alloys, etc. can be cited. As alloys, for example, nickel alloys such as nickel-copper (Ni-Cu) and nickel-aluminum (Ni-Al) can be cited.
[0044] Although not particularly limited, for example, in the use of forming the internal electrode layer of MLCC, as a conductive powder, it is preferred to use a metal species having a melting point lower than the sintering temperature of the dielectric layer (for example, about 1300°C). Among them, nickel particles are preferred from the perspective of low price and excellent balance between conductivity and cost. It should be noted that in this specification, "nickel particles" include all substances containing nickel components. As an example of nickel particles, there can be cited a single substance of nickel, the above-mentioned nickel alloy, core-shell particles with nickel particles as the core, and core-shell particles in which the surface of nickel particles is covered with precious metals such as silver.
[0045] There are no particular limitations on the method for preparing the conductive powder, the properties of the particles constituting the conductive powder, such as the size and shape of the particles. The size of the particles can be appropriately selected based on, for example, the purpose of the conductive paste, the size of the electrode layer, etc. As for the size of the particles, it is advisable to select the size in a manner that is limited to the minimum size of the target electrode layer (for example, the internal electrode layer), such as thickness and / or width, in consideration of the firing shrinkage rate. There are no particular limitations, and the average particle size D1 of the conductive powder can be about a few nm to a few μm, for example, 10 nm to 10 μm. It should be noted that the "average particle size" in this specification refers to the particle size equivalent to 50% accumulated from the side with the smaller particle size in the particle size distribution based on the number of particles observed by electron microscope.
[0046] As an example, in the use of forming the internal electrode layer of an ultra-small to small MLCC, the average particle size D1 of the conductive powder is smaller than the thickness of the internal electrode layer (the length in the stacking direction), and can be about 0.5 μm or less, typically 0.4 μm or less, and preferably 0.3 μm or less. When the average particle size D1 is below a specified value, even for a thin film electrode layer, the surface unevenness can be suppressed to a smaller level. The average particle size D1 of the conductive powder can be about 0.01 μm or more, typically 0.05 μm or more, preferably 0.1 μm or more, for example 0.2 μm or more. When the average particle size D1 is above a specified value, the surface energy of the particles is suppressed, and aggregation in the conductive paste is suppressed. Therefore, a more homogeneous coating can be achieved.
[0047] The shape of the conductive powder can be, for example, roughly spherical, flaky (sheet-like), needle-like, amorphous, etc. There is no particular limitation. In the application of forming a thin film electrode layer, the conductive powder can be roughly spherical. As a result, the viscosity of the conductive paste can be maintained at a low level, thereby improving the handleability of the paste and the operability during gravure printing. It should be noted that "roughly spherical" in this specification means that the overall shape is roughly spherical (ball), and refers to an average aspect ratio of about 1 to 2, for example, 1 to 1.5. In addition, the "aspect ratio" in this specification refers to the ratio (b / a) of the long side length (b) of the particles to the short side length (a) when the particles constituting the conductive powder are observed with an electron microscope and a rectangle circumscribed with the obtained observation image is drawn. The average aspect ratio refers to the arithmetic mean of the aspect ratios of multiple particles (for example, 100 particles).
[0048] There is no particular limitation. When the entire conductive paste is set to 100 mass %, the content of the conductive powder can be about 30 to 95 mass %, typically 35 to 80 mass %, for example 40 to 60 mass %. By satisfying the above range, the handleability of the paste and the operability during gravure printing can be improved. In addition, an electrode layer with excellent conductivity and density can be appropriately realized.
[0049] (B) Dielectric powder
[0050] The dielectric powder is a component that is placed between the conductive particles during the firing of the conductive paste to alleviate the thermal shrinkage of the conductive powder. In addition, in the use of forming the internal electrode layer of the MLCC, it can also function as a coexisting material that improves the sintering bonding between the dielectric layer and the internal electrode layer. There is no particular limitation, and the dielectric constant of the dielectric powder is typically greater than 100, for example, it can be about 1000 to 20000. However, the dielectric powder can also have a relative dielectric constant of less than 100, and can be an insulating material.
[0051] The type of dielectric powder is not particularly limited, and one or more kinds of conventionally known inorganic materials may be used alone or in appropriate combination, for example, according to the purpose. As dielectric powder, for example, metal oxides having a perovskite structure shown in ABO3, such as barium titanate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, zirconium titanate, zinc titanate, barium magnesium niobate, calcium zirconate, and strontium zirconate, titanium dioxide, titanium pentoxide, hafnium oxide, zirconium oxide, aluminum oxide, forsterite, niobium oxide, barium titanate, neodymium oxide, etc., may be cited. As an example, in the use of forming the internal electrode layer of MLCC, for example, barium titanate, strontium titanate, and calcium zirconate may be appropriately used.
[0052] There are no particular limitations on the method for preparing the dielectric powder, the properties of the particles constituting the dielectric powder, such as the size and shape of the particles. The size of the particles can be appropriately selected based on, for example, the purpose of the conductive paste, the size of the electrode layer, etc. For the size of the particles, it is appropriate to select it in a manner that is limited to the minimum size of the target electrode layer (e.g., the internal electrode layer), such as thickness and / or width, in consideration of the sintering shrinkage rate. Without particular limitations, the average particle size D2 of the dielectric powder can be about a few nm to a few μm, for example, 1 nm to 1 μm. As an example, in the use of forming the internal electrode layer of MLCC, the average particle size D2 of the dielectric powder can be about 5 nm or more, typically 10 nm or more, for example, 20 nm or more, 50 nm or more, about 0.5 μm or less, typically 0.3 μm or less, for example, 0.2 μm or less, or 0.1 μm or less.
[0053] Although not particularly limited, from the viewpoint of forming an electrode layer with excellent conductivity, the average particle size D2 of the dielectric powder is preferably smaller than the average particle size D1 of the conductive powder. That is, for D1 and D2, D1>D2 is preferably. D1 and D2 preferably satisfy (D1 / D2)≥2, more preferably satisfy (D1 / D2)≥3, for example, (D1 / D2)≥4 can be satisfied. In the case where the average particle sizes are greatly different like this, the application of the technology disclosed herein is particularly effective. In addition, D1 and D2 can satisfy 50≥(D1 / D2), can satisfy 20≥(D1 / D2), for example, 10≥(D1 / D2).
[0054] There is no particular limitation. When the entire conductive paste is set to 100 mass%, the content of the dielectric powder can be about 0.2 to 20 mass%, typically 1 to 15 mass%, for example 3 to 10 mass%. In addition, the content of the dielectric powder relative to 100 mass parts of the conductive powder can be about 3 to 35 mass parts, typically 5 to 30 mass parts, for example 10 to 25 mass parts. By satisfying the above range, the thermal shrinkage of the conductive powder can be appropriately suppressed, and a conductive layer with excellent conductivity and density can be appropriately realized.
[0055] (C) Binder resin
[0056] The binder resin is a component that adjusts the viscosity (fluidity) of the conductive paste and imparts adhesion to the coating so that the inorganic powders are closely attached to each other and to the substrate. The binder resin can be dissolved in the (D) solvent described later and functions as a vehicle. The binder resin is typically a component that disappears by firing. In other words, the binder resin is a compound that burns out during the firing of the coating. The thermal decomposition temperature of the binder resin can be, for example, 500° C. or less.
[0057] The type of binder resin is not particularly limited, and one or more types of conventionally known organic compounds used in the application can be used alone or in combination, for example, according to the application. The binder resin is typically a thermoplastic resin. However, it can also be a thermosetting resin. As the binder resin, for example, organic polymer compounds such as cellulose resins, polyvinyl acetal resins, polyvinyl alcohol resins, acrylic resins, urethane resins, epoxy resins, phenolic resins, rosin resins, polyester resins, and vinyl resins can be cited. Among them, from the perspective of improving the burnout during firing and the surface smoothness of the electrode layer, as the binder resin, it is preferred to include (C1) cellulose resin. In addition, in the conductive paste containing inorganic powder of fine particle size as described above, from the perspective of improving the adhesion between the coating and the substrate and the integrity of the coating, as the binder resin, it is preferred to include (C2) polyvinyl acetal resin, for example, it is appropriate to use (C1) cellulose resin and (C2) polyvinyl acetal resin in combination.
[0058] (C1) Cellulose resins include all straight-chain polymers (cellulose) having β-glucose as repeating units, and derivatives thereof. (C1) Cellulose resins can typically be compounds in which part or all of the hydroxyl groups in the β-glucose structure as a repeating unit are replaced by alkoxy groups, and derivatives thereof (modified substances, etc.). It should be noted that, for the alkyl or aryl (R) in the alkoxy group (RO-), part or all of them can be replaced by ester groups such as carboxyl groups, nitro groups, halogens, and other organic groups. As cellulose resins, for example, methyl cellulose (MC), ethyl cellulose (EC), hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, carboxyethyl cellulose, carboxyethyl methyl cellulose, cellulose acetate phthalate, nitrocellulose, etc. can be cited. Among them, MC and EC are preferred. By including cellulose resins, it is possible to improve the operability during gravure printing and stably form a coating film with excellent surface smoothness.
[0059] The properties of the cellulose resin are not particularly limited. The weight average molecular weight (Mw) of the cellulose resin may be about 10,000 or more, for example, 60,000 or more, 80,000 or more, 120,000 or more, or 200,000 or more. In addition, the weight average molecular weight (Mw) of the cellulose resin may be about 800,000 or less, for example, 600,000 or less, 400,000 or less, or 320,000 or less. It should be noted that the "weight average molecular weight (Mw)" is an average molecular weight based on the number of units, which can be measured, for example, by gel permeation chromatography (GPC) and calculated using a standard polystyrene standard curve.
[0060] (C2) Polyvinyl acetal resin is a resin obtained by acetalizing a polyvinyl alcohol resin with an aldehyde. Polyvinyl acetal resin includes all of the following substances: a polymer having a structural unit formed by acetalizing a continuous vinyl alcohol structural unit using an aldehyde compound, and having one or more of an unreacted vinyl alcohol structural unit and a vinyl acetate structural unit as an unsaponified portion of the polyvinyl alcohol resin, and a derivative (modified product, etc.) thereof. The proportion of the acetalized structural unit in the polyvinyl acetal resin (acetalization degree) can be, for example, 50 mol% or more. Polyvinyl acetal resin is superior in adhesion and flexibility compared to, for example, cellulose resins.
[0061] As the polyvinyl acetal resin, for example, polyvinyl butyral resin (PVB) having a structure in which polyvinyl alcohol is acetalized with butanol can be cited. By including PVB, the shape characteristics of the coating film can be improved. The polyvinyl acetal resin can be a copolymer (including graft copolymerization) containing a polyvinyl acetal resin as a main monomer (a component that occupies more than 50% of the total monomer. The same applies hereinafter) and a secondary monomer copolymerizable with the main monomer. As the secondary monomer, for example, ethylene, ester, (meth)acrylate, vinyl acetate, etc. can be cited.
[0062] The properties of the polyvinyl acetal resin are not particularly limited. The weight average molecular weight (Mw) of the polyvinyl acetal resin can be about 50,000 or more, for example, it can be 75,000 or more, 85,000 or more, 100,000 or more, or 150,000 or more. In addition, the weight average molecular weight (Mw) of the polyvinyl acetal resin is about 1,000,000 or less, for example, it can be 750,000 or less, 500,000 or less, preferably 300,000 or less, 250,000 or less, for example, 200,000 or less. By setting the weight average molecular weight to below the specified value, the increase in the viscosity of the paste can be appropriately suppressed. Therefore, it is possible to take into account both gravure printability and the shape characteristics of the coating film at a high level.
[0063] Without particular limitation, the binder resin may also be composed of (C2) polyvinyl acetal resin as the main component (the component with the largest content. The same applies below). When the binder resin as a whole is set to 100% by mass, the (C2) polyvinyl acetal resin may occupy about 50% by mass or more, for example, 60 to 80% by mass. In addition, when both (C1) cellulose resin and (C2) polyvinyl acetal resin are included as binder resins, when (C1) + (C2) is set to 100% by mass, the (C2) polyvinyl acetal resin may be about 10 to 90% by mass, typically 20 to 80% by mass, for example, 50 to 70% by mass.
[0064] There is no particular limitation. When the conductive paste is set to 100% by mass as a whole, the content of the binder resin can be about 0.1 to 5% by mass, typically 1 to 4% by mass, for example 2 to 3% by mass. In addition, the content of the binder resin relative to 100 parts by mass of the conductive powder can be about 0.1 to 10 parts by mass, typically 0.5 to 8 parts by mass, for example 1 to 7 parts by mass, 2 to 5 parts by mass. By satisfying the above range, the conductive paste is easily adjusted to a property suitable for gravure printing. In addition, the adhesion between the coating film and the substrate can be improved, thereby stably realizing a conductive layer with excellent conductivity and compactness.
[0065] (D) Solvent
[0066] The solvent is a liquid medium for dispersing the inorganic powder and imparting a viscosity (fluidity) suitable for gravure printing to the conductive paste. In addition, the solvent can also function as a carrier for dissolving the above-mentioned (C) binder resin and / or the (E) dispersant described later. The solvent is typically a component that disappears by drying and firing. The solvent is a component that burns out when the conductive paste is dried and / or the coating is fired. The type of solvent is not particularly limited, and one or more types of organic solvents known in the past used in this application can be used alone or in combination according to, for example, the type of substrate, (C) binder resin, etc. As a solvent, for example, an alcohol solvent having an -OH group, an ether solvent having an ether bond (RO-R'), an ester solvent having an ester bond (RC(=O)-O-R'), a hydrocarbon solvent composed of carbon atoms and hydrogen atoms, etc. can be cited.
[0067] Examples of the alcohol solvent and the ether solvent include terpineol, texanol, dihydroterpineol, benzyl alcohol, 3-methoxy-3-methyl-1-butanol, phenoxyethanol, 1-phenoxy-2-propanol, isoborneol, diethylene glycol, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether (butyl carbitol), propylene glycol monobutyl ether, and dipropylene glycol methyl-n-propyl ether. Examples of the ester solvent include 3-methoxy-3-methyl-1-butanol acetate, 3-methoxybutyl acetate, ethylene glycol monomethyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol diacetate, cyclohexanol acetate, isobornyl acetate, carbitol acetate, ethyl diglycol acetate, butyl glycol acetate, butyl diglycol acetate, butyl cellosolve acetate, diethylene glycol monobutyl ether acetate (butyl carbitol acetate), terpineol acetate, dihydroterpineol acetate, etc. Examples of the hydrocarbon solvent include aromatic hydrocarbon solvents such as toluene and xylene; alkane solvents such as normal paraffins and isoparaffins; cycloalkane solvents such as monocyclic cycloalkanes and bicyclic cycloalkanes; alkane / cycloalkane mixed solvents; and aliphatic hydrocarbon solvents such as mineral spirits.
[0068] Although not particularly limited, when a conductive paste is applied to a raw sheet, from the viewpoint of suppressing the sheet erosion phenomenon (the phenomenon of the solvent eroding the raw sheet), as a solvent, a hydrocarbon solvent is preferably included. For example, it is appropriate to use a combination of a hydrocarbon solvent and a solvent other than a hydrocarbon solvent, such as an alcohol solvent and an ester solvent. Among them, the hydrocarbon solvent preferably includes a cycloalkane solvent, and the hydrocarbon solvent can be composed of a cycloalkane solvent as a main component. When the entire hydrocarbon solvent is set to 100% by mass, the cycloalkane solvent can occupy about 50% by mass or more, for example, 60 to 80% by mass. In addition, when a hydrocarbon solvent and a solvent other than a hydrocarbon solvent are included as solvents at the same time, when the total of the hydrocarbon solvent and the solvent other than the hydrocarbon system is set to 100% by mass, the content ratio of the solvent other than the hydrocarbon system can be about 10 to 95% by mass, typically 20 to 90% by mass, for example, 50 to 80% by mass.
[0069] Although not particularly limited, from the viewpoint of improving the storage stability of the conductive paste, the operability during gravure printing, etc., the solvent other than the hydrocarbon system preferably contains a high boiling point solvent having a boiling point of about 100°C or more, for example, 200°C or more. In addition, if the viewpoint of rapidly drying the coating film to improve productivity is considered, it is preferable to use a high boiling point solvent having a boiling point of about 100 to 300°C, for example, 200 to 250°C, preferably 230°C or less as the main component. When the total amount of the solvent other than the hydrocarbon system is 100% by mass, the high boiling point solvent may occupy about 50% by mass or more, for example, 90% by mass or more, or substantially the entire solvent (95% by mass or more) may be composed of the high boiling point solvent.
[0070] In addition, from the viewpoint of adjusting the conductive paste to a property suitable for gravure printing and achieving good balance between sheet corrosiveness, solvents other than hydrocarbons include an SP value of about 10.5 (cal / cm 3 ) 0.5 Below, for example, 10 (cal / cm 3 ) 0.5 Below, preferably 9.9 (cal / cm 3 ) 0.5 Below, for example, 8 to 9.9 (cal / cm 3 ) 0.5 From the viewpoint of the solubility of the resin, the SP value of the solvent other than the hydrocarbon system can be about 8 (cal / cm 3 ) 0.5 Above, for example, 8.5 (cal / cm 3 ) 0.5 Above, it can be 9 (cal / cm 3 ) 0.5In addition, from the perspective of better suppressing sheet erosion, the SP value of the solvent other than hydrocarbons can be about 9.8 (cal / cm 3 ) 0.5 Below, for example 9.7 (cal / cm 3 ) 0.5 the following.
[0071] The solvent other than the hydrocarbon system may include a first solvent and a second solvent having different boiling points and / or SP values. For example, the first solvent having excellent solubility in the binder resin and the second solvent having excellent quick-drying properties may be included. The SP value of the first solvent is higher than that of the second solvent, and may be about 10.0 (cal / cm 3 ) 0.5 Above, for example, 10 to 10.5 (cal / cm 3 ) 0.5 In addition, the boiling point of the first solvent may be about 200°C or more, for example, 200 to 230°C. The boiling point of the second solvent is equal to or lower than that of the first solvent, and may be about 220°C or less, for example, 140 to 215°C. In addition, the SP value of the second solvent may be about 9.5 (cal / cm 3 ) 0.5 Below, for example, it can be 8.5 to 9.5 (cal / cm 3 ) 0.5 . Thus, the dispersibility of the inorganic powder in the conductive paste, the solubility of the binder resin, and the drying property of the coating film can be achieved at a high level. When the total of the first solvent and the second solvent is set to 100 mass %, the content ratio of the first solvent can be about 10 to 95 mass %, typically 20 to 90 mass %, for example, 50 to 80 mass %.
[0072] There is no particular limitation. When the entire conductive paste is 100% by mass, the content of the solvent may be about 80% by mass or less, typically 10 to 70% by mass, for example 30 to 60% by mass. By satisfying the above range, the conductive paste can be given appropriate fluidity, and the operability during gravure printing can be improved. In addition, the self-leveling property can be improved, so that a coating film with excellent surface smoothness can be stably formed even during high-speed printing.
[0073] (E) Dispersant
[0074] The dispersant is an amphiphilic compound used to uniformly disperse the inorganic powders, i.e., (A) conductive powder and (B) dielectric powder, in the conductive paste to inhibit aggregation of these components. The dispersant can dissolve in the above-mentioned (D) solvent and function as a carrier. Thus, the inorganic powders can be uniformly and stably dispersed.
[0075] The conductive paste disclosed herein contains a dicarboxylic acid-based dispersant having a structural portion represented by the following formula (1) as a dispersant.
[0076]
[0077] In formula (1), A 1 , A 2 Each is independently hydrogen (H); an alkali metal such as sodium (Na) or potassium (K); or an alkaline earth metal such as magnesium (Mg) or calcium (Ca). 1 , A 2 They may all be hydrogen.
[0078] In the structural part of formula (1), a carboxylate group (—C(═O)O) is bonded to the second and third carbon atoms from the right, respectively. - ). That is, the carboxylate groups are bonded to adjacent carbon atoms, respectively. In addition, no substituent is bonded to the fourth carbon atom (the leftmost carbon atom) adjacent to the third carbon atom. That is, it is represented by -CH2. The details are not yet clear, but it is believed that by using a dicarboxylic acid dispersant having such a structural part, the uniform dispersibility of the inorganic powder in the conductive paste can be significantly improved compared with the use of other anionic dispersants (for example, monocarboxylic acid dispersants, dicarboxylic acid dispersants that do not have the structural part of the above formula (1), polycarboxylic acid dispersants, sulfonic acid dispersants, phosphoric acid dispersants, etc.) and amine dispersants.
[0079] That is, by making two carboxylic acid ester groups close to each other in the same molecule, the probability of bonding to the surface of (A) conductive powder and (B) dielectric powder is increased. Therefore, it is believed that the dispersant is more adsorbed on the surface of the inorganic powder, thereby stabilizing the inorganic particles. In addition, in the dispersant having the structural part of the above formula (1), it is believed that there are two carboxylic acid ester groups, both of which are adsorbed on inorganic particles, and one side is adsorbed on inorganic particles and the other side becomes an unadsorbed state through equilibrium reaction, but the latter is considered to be dominant in probability. Therefore, it is believed that, for example, when the (B) dielectric powder is a microparticle compared to the (A) conductive powder, the dispersant disclosed herein is easily adsorbed on the surface of the (B) dielectric powder in a state of being charged due to the unadsorbed carboxylic acid ester group. Moreover, it is believed that the unadsorbed carboxylic acid ester group interacts electrically with the (A) conductive powder, so that the (A) conductive powder and the (B) dielectric powder are uniformly dispersed without bias.
[0080] The properties of the dispersant are not particularly limited. The molecular weight of the dispersant may be about 100 or more, for example, 150 or more, 200 or more, or 230 or more. In addition, the molecular weight of the dispersant may be about 20,000 or less, for example, about 10,000 or less, 5,000 or less, 2,000 or less, 1,000 or less, or 500 or less. By setting the molecular weight to be above the prescribed value, the effect of providing uniform dispersibility of the above-mentioned inorganic powder can be better exerted. In addition, by setting the molecular weight to be below the prescribed value, the increase in the viscosity of the paste can be appropriately suppressed. For the dispersant, a low molecular weight compound having a molecular weight of less than 10,000 is preferably used compared to a high molecular weight compound having a molecular weight of more than 10,000. Thus, the above-mentioned effect can be exerted at a higher level.
[0081] It should be noted that, in this specification, when referred to as "molecular weight", it refers to the value calculated by calculation based on the sum of the atomic weights of each atom based on the molecular formula. It should be noted that the molecular formula of the compound can be determined by appropriately selecting an analytical method corresponding to the molecular structure. As an example of an analytical method, infrared spectroscopy (IR: Infrared Spectroscopy), nuclear magnetic resonance (NMR: Nuclear Magnetic Resonance), mass spectrometry (MS: Mass Spectrometry), gas chromatography-mass spectrometry (GC-MS: Gas Chromatography-Massspectrometry), gas chromatography (GC: Gas Chromatography), gel permeation chromatography (GPC: Gel Permeation Chromatography), CHN elemental analysis, etc. can be cited.
[0082] The dispersant is not particularly limited except for having a structural part of formula (1), and can be used alone or in combination of two or more of the conventionally known amphiphilic compounds used for such purposes. An example of the dispersant is a compound represented by the following formula (2).
[0083]
[0084] In formula (2), A 1 , A 2 Same as the above formula (1). In addition, R is a saturated or unsaturated aliphatic group having 3 to 30 carbon atoms. The carbon number may be, for example, 4 or more, 5 or more, 6 or more, or 7 or more, or may be, for example, 29 or less, 28 or less, 27 or less, or 25 or less. The aliphatic group may be straight-chain or branched. Examples of the aliphatic group include alkyl, alkenyl, alkynyl, and the like. The aliphatic group may include vinylene (-CH=CH-).
[0085] Specific examples of the dispersant represented by the above formula (2) include octenyl butane dioic acid (C 12 H 20 O4: molecular weight = 228), octadecenylbutane dioic acid (C 22 H 40 O4: molecular weight = 368), hexacosenoylbutane dioic acid (C 30 H 56 O4: molecular weight = 480) etc. It should be noted that in the following formula (3), the R portion of formula (2) is a straight-chain alkenyl group having 7 carbon atoms, in the following formula (4), the R portion of formula (2) is a straight-chain alkenyl group having 17 carbon atoms, and in the following formula (5), the R portion of formula (2) is a straight-chain alkenyl group having 25 carbon atoms.
[0086]
[0087] The dispersant may have a compound having a structural part of the above-mentioned formula (1) as a main component. When the entire dispersant is set to 100% by mass, the compound having a structural part of formula (1) may occupy about 50% by mass or more, and the entire dispersant (95% by mass or more) may be substantially composed of a compound having a structural part of formula (1). However, as long as the dispersant does not significantly reduce the technical effect disclosed herein, other compounds may be auxiliary included. As an example of a dispersant that may be auxiliary included, anionic dispersants such as monocarboxylic acid dispersants, dicarboxylic acid dispersants not having a structural part of the above-mentioned formula (1), polycarboxylic acid dispersants, sulfonic acid dispersants, phosphoric acid dispersants, and amine dispersants may be cited. These auxiliary dispersants may be suppressed to less than about 50% by mass, less than 30% by mass, less than 10% by mass, for example, less than 5% by mass of the entire dispersant.
[0088] There is no particular limitation. When the entire conductive paste is set to 100 mass%, the content of the dispersant can be about 0.01 to 5 mass%, typically 0.05 to 3 mass%, for example 0.1 to 2 mass%, preferably 0.5 mass% or less, for example 0.3 mass% or less, 0.2 mass% or less. By setting the content of the dispersant to a predetermined value or more, the dispersant can be fully applied to the fine inorganic powder. In addition, by setting the content of the dispersant to a predetermined value or less, an electrode layer with excellent conductivity and compactness can be appropriately realized.
[0089] (F) Other additives
[0090] The conductive paste disclosed herein may be composed of the above four components, and may contain various additives that can be used in conventional conductive pastes as long as the essence of the present invention is not significantly impaired. As an example of such additives, for example, viscosity modifiers, thickeners, defoamers, plasticizers, leveling agents, pH adjusters, stabilizers, antioxidants, preservatives, colorants (pigments, dyes, etc.), etc. These additives may be used alone or in combination of two or more as needed.
[0091] The additives may be contained in an appropriate proportion according to the purpose of addition, etc. There is no particular limitation, but when the entire conductive paste is set to 100 mass %, the content of the additives may be suppressed to about 5 mass % or less, typically 3 mass % or less, for example 1 mass % or less. Thus, an electrode layer with excellent conductivity and compactness can be appropriately realized.
[0092] (G) Properties of Conductive Paste
[0093] The conductive paste disclosed herein is adjusted to a low viscosity for gravure printing with a fast printing speed. Specifically, at 25°C, the shear rate is 40 s -1 Viscosity V 40 The viscosity V is adjusted to 5 Pa·s or less. From the viewpoint of increasing the printing speed and improving productivity, the viscosity V 40 The viscosity V can be adjusted to, for example, 4.5 Pa·s or less, 4 Pa·s or less, 3.5 Pa·s or less, or 3 Pa·s or less. From the viewpoint of suppressing printing collapse and improving operability, the viscosity V 40 It can be adjusted to, for example, 0.1 Pa·s or more, 0.2 Pa·s or more. It should be noted that the viscosity of the conductive paste can be adjusted by, for example, the type and content of the binder resin, the type and content of the dispersant, the type and content of the solvent, the addition of other additives (such as viscosity modifiers, thickeners), etc.
[0094] No special restrictions, at 25 ° C, shear rate 4s -1 The viscosity V4 can be adjusted to about 20 Pa·s or less, 18 Pa·s or less, 15 Pa·s or less, or 13 Pa·s or less. The viscosity V4 can be adjusted to, for example, 0.1 Pa·s or more, 0.2 Pa·s or more, or 0.4 Pa·s or more. 40 The ratio (V4 / V 40 ) may be about 7 or less, typically 6 or less, for example 5.5 or less, 5 or less, or 4.5 or less. This can improve the storage stability and handling properties of the conductive paste.
[0095] Such a conductive paste can be suitably prepared, for example, by preparing a carrier in which (C) a binder resin and (E) a dispersant are dispersed or dissolved in (D) a solvent, adding (A) a conductive powder and (B) a dielectric powder thereto, and stirring and mixing. Various conventionally known stirring devices and dispersing devices, such as a ball mill, a bead mill, a roller mill, a magnetic stirrer, a planetary mixer, a disperser, a high-pressure disperser, a mortar, etc., can be appropriately used in the preparation of the conductive paste.
[0096] (H) Properties of coating film
[0097] The coating formed using the conductive paste disclosed herein can suppress the surface unevenness to be smaller than before. Although it also depends on the particle size of the inorganic powder, the maximum roughness Rmax of the coating can be, for example, less than 0.7μm, preferably less than 0.65μm, or less than 0.6μm. In addition, the coating formed using the conductive paste disclosed herein has excellent dispersibility of the inorganic powder and can have a homogeneous composition compared to the past. Although it also depends on the particle size of the inorganic powder, the dispersion index of the inorganic powder in the coating can be, for example, more than 80%, preferably more than 83%, or more than 89%. It should be noted that the method for measuring the maximum roughness Rmax and the method for calculating the dispersion index are described in the embodiments described later.
[0098] [Application of conductive paste]
[0099] The conductive paste disclosed herein can be used for the following purposes: it is applied to any substrate by gravure printing and dried to form a coating film, which is fired to form an electrode layer. Among them, it can be preferably used in applications requiring surface smoothness and homogeneity of the electrode layer. As a representative use, the formation of internal electrode layers of small laminated ceramic electronic components with each side being less than 5 mm, for example, less than 1 mm can be cited. In particular, it can be appropriately used for the formation of internal electrode layers of small and large-capacity MLCCs in which the thickness of the dielectric layer is thinned to a level of less than 2 μm.
[0100] It should be noted that in this specification, "ceramic electronic components" include all electronic components having a crystalline ceramic substrate and / or an amorphous ceramic substrate. For example, ceramic capacitors, chip inductors, high-frequency filters, high-temperature co-fired ceramic substrates (HTCC) substrates, low-temperature co-fired ceramic substrates (LTCC) substrates, etc., which include ceramic substrates, are typical examples of "ceramic electronic components" mentioned here.
[0101] Examples of the ceramic material constituting the ceramic substrate include barium titanate (BaTiO3), strontium titanate (SrTiO3), calcium titanate (CaTiO3), calcium zirconate (CaZrO3), strontium zirconate (SrZrO3), zirconium oxide (zirconium oxide: ZrO2), magnesium oxide (magnesium oxide: MgO), aluminum oxide (aluminum oxide: Al2O3), silicon dioxide (silica: SiO2), zinc oxide (ZnO), titanium oxide (titanium dioxide: TiO2), cerium oxide (cerium dioxide: CeO2), Oxide materials such as yttrium oxide (yttrium oxide: Y2O3) and gadolinium oxide (Gd2O3); composite oxide materials such as cordierite (2MgO·2Al2O3·5SiO2), mullite (3Al2O3·2SiO2), forsterite (2MgO·SiO2), steatite (MgO·SiO2), sialon (Si3N4-AlN-Al2O3), zircon (ZrO2·SiO2), and ferrite (M2O·Fe2O3); nitride materials such as silicon nitride (silicon nitride: Si3N4), aluminum nitride (aluminum nitride: AlN), and boron nitride (boron nitride: BN); carbide materials such as silicon carbide (silicon carbide: SiC) and boron carbide (boron carbide: B4C); hydroxide materials such as hydroxyapatite; etc. These may be contained alone or in the form of a mixture of two or more thereof, or in the form of a complex of two or more thereof.
[0102] [Multilayer Ceramic Capacitors]
[0103] Figure 1 The cross-sectional view schematically shows the structure of a stacked ceramic capacitor (MLCC) 1. MLCC1 is a chip-type capacitor composed of a plurality of dielectric layers 20 and internal electrode layers 30 alternately stacked integrally. A pair of external electrodes 40 are provided on the side of the stacked chip 10 including the dielectric layer 20 and the internal electrode layer 30. As an example, the internal electrode layer 30 is alternately connected to different external electrodes 40 in a stacking order. Thus, a capacitor structure including a dielectric layer 20 and a pair of internal electrode layers 30 sandwiching the dielectric layer 20 is connected in parallel to construct a small and large-capacity MLCC1. The dielectric layer 20 of MLCC1 is composed of, for example, a dielectric material. The internal electrode layer 30 is composed of a sintered body of the conductive paste disclosed herein. Such an MLCC1 can be manufactured, for example, according to the following steps.
[0104] Figure 2This is a cross-sectional view schematically showing the structure of an unfired laminated body 10a (in other words, an unfired laminated chip 10). When manufacturing MLCC1, first, a dielectric green sheet as a substrate is prepared. Here, for example, a ceramic powder, a binder resin, a solvent, etc. as a dielectric material are mixed to prepare a paste for forming a dielectric layer. Next, the prepared paste is applied to a carrier sheet in a thin layer by a doctor blade method, etc., thereby preparing an unfired dielectric green sheet 20a. Next, prepare the conductive paste disclosed herein. Then, the prepared conductive paste is applied to the dielectric green sheet 20a in a prescribed pattern and in a manner to a desired thickness (for example, less than 1 μm) to form a coating 30a. Using the conductive paste disclosed herein, the dispersibility of the inorganic powder is good, and a coating 30a with excellent surface smoothness and good adhesion to the dielectric green sheet can be stably formed.
[0105] Next, a plurality of (e.g., several hundred to several thousand) prepared dielectric green sheets 20a with coating films 30a are stacked and crimped. Thus, a stacked and crimped body is produced. The stacked and crimped body is cut into a chip shape as required. Since the coating film 30a has small surface irregularities, deformation of the stacked structure is not likely to occur even if stacked or crimped. In addition, the coating film 30a has good adhesion to the dielectric green sheet 20a, so even if stacked, crimped or cut, the coating film 30a is not likely to break or peel off. Thus, an unfired stack 10a can be obtained stably.
[0106] Next, the unfired laminate 10a is fired under appropriate heating conditions (for example, in an atmosphere containing nitrogen and hydrogen at a temperature of about 1000 to 1300°C). Thus, the dielectric green sheet 20a is fired to form the dielectric layer 20 (see Figure 1 ). In addition, the coating film 30a is fired to form the internal electrode layer 30 (refer to Figure 1 ). In this way, the dielectric layer 20 and the internal electrode layer 30 are sintered integrally, and the laminated chip 10 can be obtained. According to the technology disclosed herein, the internal electrode layer 30 can be formed into an electrically continuous and homogeneous layer. Thereafter, the external electrode material is applied to the side of the laminated chip 10 and sintered to form the external electrode 40. By operating as described above, a high-quality MLCC 1 that is not prone to defects such as short circuits can be manufactured.
[0107] Hereinafter, some embodiments related to the present invention will be described, but the present invention is not intended to be limited to the embodiments.
[0108] <Test Example I>
[0109] [Preparation of Conductive Paste]
[0110] In this test example, (A) conductive powder, (B) dielectric powder, (C) binder resin, (D) solvent and (E) dispersant were stirred and mixed to prepare conductive pastes (Comparative Examples 1 to 9, Examples 1 to 3) in which only the type of the dispersant (E) was different.
[0111] As the conductive powder (A), nickel powder (Ni) having an average particle size of 0.2 μm was used so as to be 50% by mass relative to the entire conductive paste.
[0112] As the dielectric powder (B), barium titanate powder (BT) having an average particle size of 50 nm was used in an amount of 15 parts by mass relative to 100 parts by mass of the nickel powder.
[0113] As the binder resin (C), ethyl cellulose (EC) and polyvinyl butyral (PVB, weight average molecular weight (Mw): 85,000) were mixed and used. It should be noted that in Comparative Examples 1 and 2, a portion of high molecular weight ethyl cellulose was used to adjust the viscosity to high. EC was used in a ratio of 2 parts by mass relative to 100 parts by mass of nickel powder, and PVB was used in a ratio of 3 parts by mass relative to 100 parts by mass of nickel powder.
[0114] As the (D) solvent, a hydrocarbon solvent (cycloalkane solvent) and a first solvent (dihydroterpineol) and a second solvent (3-methoxy-3-methyl-1-butanol acetate) as solvents other than hydrocarbons are mixed in a mass ratio of first solvent: second solvent: hydrocarbon solvent = 45:30:25, and the remainder after deducting (A) conductive powder, (B) dielectric powder, (C) binder resin, and (E) dispersant is used as the proportion of the (D) solvent in the conductive paste.
[0115] As the (E) dispersant, the substances shown in Table 1 were used in a ratio of 0.2% by mass relative to the entire paste. It should be noted that the "comb carboxylic acid" used in Comparative Example 4 is a polymer of hydroxystearic acid, and the structural formulas of "N-oleoylsarcosine", "malonic acid", "citric acid" and "oleic acid" used in Comparative Examples 5 to 8 are respectively shown in the following formula (6), formula (7), formula (8) and formula (9).
[0116]
[0117] [Measurement of paste viscosity]
[0118] The viscosity of the conductive paste was measured using a rotational vibration rheometer MARS III manufactured by HAAKE. The measurement conditions were as follows: a shear rate of 40 s -1 Viscosity V 40 (Pa·s) and shear rate 4s-1 The viscosity V4 (Pa·s) at the time of 0.05 is shown in the "Viscosity" column of Table 1. 40 The ratio (V4 / V 40 ) are shown in the "Viscosity Ratio" column of Table 1.
[0119] Measurement mode: Shear rate dependent measurement
[0120] Sensor: Cone-plate ( Angle 1°)
[0121] Measurement temperature: 25℃
[0122] Gap: 0.052mm
[0123] Shear speed: 10000~0.01s -1
[0124] Measurement time: 3 minutes
[0125] [Evaluation of dispersion index]
[0126] The coating film was formed according to the following steps, and the dispersibility of the inorganic powder (here, conductive powder) in the coating film was evaluated. Specifically, first, the conductive paste of each example was applied to the PET substrate with a thickness of about 250 μm using an applicator, and dried at 110°C for about 15 minutes to form a coating film (about 50 μm). Then, the coating film was observed by SEM from the side of the PET substrate to obtain an SEM observation image. It should be noted that the acceleration voltage during observation was set to 20 kV and the observation magnification was set to 10,000 times. Figure 3 This is an example of a SEM observation image. Figure 3 (A) is the SEM observation image of Comparative Example 3, Figure 3 (B) is a SEM observation image of Comparative Example 9.
[0127] Next, based on the obtained SEM observation image, the dispersion index of the conductive powder is calculated according to a conventionally known dispersibility evaluation method (for example, see Japanese Patent Application Publication No. 2015-7542). That is, first, the SEM observation image is binarized using a predetermined threshold value to generate an evaluation image. Figure 4A conceptual diagram for explaining the method of calculating the dispersion index. Next, the evaluation image is partitioned into equal-sized partitions until the number of partitions is specified, and the evaluation image variation coefficient CVb and the complete separation variation coefficient CVa are calculated for each partition size. It should be noted that the evaluation image variation coefficient CVb is calculated based on the area value x of the object (for example, the white part after binarization representing the conductive powder) and the standard deviation σ. In addition, the complete separation variation coefficient CVa is calculated based on the area value of the object when it is assumed that the object is completely separated from non-objects other than the object. In addition, here, the evaluation image is partitioned until the evaluation image variation coefficient CVb is the same value as the complete separation variation coefficient CVa. In addition, for each partition size, the complete mixing variation coefficient CVc is calculated based on the area value of the object when it is assumed that the object is completely mixed with non-objects other than the object.
[0128] Next, plot the partition size and evaluation image variation coefficient CVb on the two-dimensional coordinates, connect the values of the evaluation image variation coefficient CVb between adjacent partition sizes with a straight line, and Figure 4 Similarly, plot the partition size and the coefficient of variation CVa when completely separated on a two-dimensional coordinate system, and connect the values of the coefficient of variation CVa when completely separated between adjacent partition sizes with a straight line. Figure 4 In addition, the partition size and the coefficient of variation CVc when completely mixed are plotted on the two-dimensional coordinates, and the values of the coefficient of variation CVc when completely mixed are connected with straight lines between adjacent partition sizes. Figure 4 The “third relationship c” is graphed.
[0129] Next, in the first relationship b, the second relationship a, and the third relationship c, the integral value of the range from the minimum partition size (i.e., the maximum number of partitions) to the maximum partition size (i.e., the minimum number of partitions) is calculated. Figure 4 As shown, the area surrounded by the first relationship b and the horizontal axis is set to B, the area surrounded by the second relationship a and the horizontal axis is set to A, and the area surrounded by the third relationship c and the horizontal axis is set to C. Then, the dispersion index is calculated based on the following formula: dispersion index α [%] = (1-(BC) / (AC)) × 100. The results are shown in the "Dispersion Index α" column of Table 1. It should be noted that the closer the dispersion index α is to 100%, the better the dispersibility of the conductive powder in the coating film is (that is, the conductive powder is highly dispersed close to a completely mixed state).
[0130] Then, the dispersibility of the coating film of each example was evaluated based on the following indexes. The results are shown in the "Dispersibility Index-Judgment" column of Table 1.
[0131] ×: α less than 89%
[0132] ○: α is 89% or more
[0133] [Evaluation of gravure printing properties]
[0134] The coating film was formed according to the following steps, and the surface roughness of the coating film was measured. Specifically, first, a dielectric green sheet containing barium titanate was prepared. Then, a conductive paste with a dispersion index of "0" was applied to the dielectric green sheet with a thickness of about 1 μm by gravure printing, and dried at 80°C for about 5 minutes to form a coating film. It should be noted that the conditions for gravure printing are as follows.
[0135] Printing pattern: 1005type (2000μm×500μm)
[0136] Printing speed: 30m / min
[0137] Printing pressure: 0.3MPa
[0138] Next, the surface roughness of the coating is measured using a super-resolution non-contact three-dimensional surface shape measurement system (model: BW-A501) manufactured by Nikon Corporation. The measurement conditions are as follows. Then, the height image of the coating is imported and analyzed to obtain a cross-sectional profile. For the cross-sectional profile, 5 locations (n=5) are prepared for each sample. Then, the difference between the highest point and the lowest point of the obtained cross-sectional profile is calculated, and the arithmetic mean of n=5 is taken as the "maximum roughness Rmax". The results are shown in the "Rmax" column of Table 1.
[0139] · Optical microscope: Interference microscope manufactured by Nikon Corporation (model: ECLIPSE LV150)
[0140] Objective lens magnification: 10 times
[0141] ·Measurement range: 50μm×1000μm
[0142] Figure 6 is an example of a cross-sectional profile of surface roughness. Figure 6 (A) is the cross-sectional profile of Comparative Example 3, Figure 6 (B) is the cross-sectional profile of Example 1. Then, the gravure printability of the conductive paste of each example was evaluated based on the following indexes. The results are shown in the "Gravure Printability-Judgment" column of Table 1.
[0143] ×: Rmax exceeds 0.7 μm
[0144] ○: Rmax is 0.7 μm or less
[0145] [Comprehensive judgment]
[0146] In addition, a comprehensive evaluation was performed based on the evaluation results of the above-mentioned dispersion index and the evaluation results of the gravure printing properties. For the comprehensive evaluation, the case where both of the above-mentioned two evaluation results are ○ is recorded as "○", and the case where even one of them includes × is recorded as "×". The results are shown in the "Comprehensive Judgment" column of Table 1.
[0147] [Table 1]
[0148] Table 1
[0149]
[0150] *: The polycarboxylic acids of Comparative Examples 1 and 10 are weight average molecular weights.
[0151] As shown in Table 1, although the conductive pastes of Comparative Examples 1 to 3 have excellent dispersibility in the coating film, the surface of the coating film has large irregularities and lacks gravure printability. In addition, the conductive pastes of Comparative Examples 4 to 9 have insufficient dispersibility in the coating film. In contrast, the conductive pastes of Examples 1 to 3 contain a predetermined dicarboxylic acid dispersant and set the viscosity V 40 By adjusting the viscosity to 5 Pa·s or less and keeping it low, both the homogeneity of the coating film and the gravure printability can be achieved.
[0152] <Test Example II>
[0153] In this test example, except that the first solvent (dihydroterpineol) and the hydrocarbon solvent (cycloalkane solvent) were mixed and used at a mass ratio of the first solvent: hydrocarbon solvent = 75:25 as the (D) solvent, the same operation as in Example 2 was carried out to prepare a conductive paste (Example 4), and the evaluation was carried out in the same manner as in Test Example 1. The results are shown in Table 2.
[0154] [Table 2]
[0155] Table 2
[0156]
[0157] As shown in Table 2, it was confirmed that, in Example 4 in which the second solvent (3-methoxy-3-methyl-1-butanol acetate) was not used, similarly to Example 2, both the homogeneity of the coating film and the gravure printability could be achieved.
[0158] <Test Example III>
[0159] In this test example, an inorganic powder having a larger particle size than that of Test Examples I and II was used to prepare a conductive paste (Comparative Example 11, Examples 5 to 8). Specifically, as (A) conductive powder, nickel powder (Ni) having an average particle size of 0.3 μm was used in a ratio of 50% by mass relative to the entire conductive paste. In addition, as (B) dielectric powder, barium titanate powder (BT) having an average particle size of 100 nm was used in a ratio of 25 parts by mass relative to 100 parts by mass of nickel powder. In Comparative Example 11 and Example 5, conductive pastes were prepared in the same manner as Comparative Example 4 and Example 2, respectively. In Examples 6 and 7, the formulation of the binder resin (C) was made different as shown in Table 3, and conductive pastes were prepared in the same manner as Example 5. In Example 8, the content ratio of the conductive powder (A) was set to 57% by mass relative to the entire conductive paste, and conductive pastes were prepared in the same manner as Example 5.
[0160] Then, evaluation was performed in the same manner as in Test Example 1. The results are shown in Table 3. Figure 5 This is an example of a SEM observation image. Figure 5 (A) is the SEM observation image of Example 5, Figure 5 (B) is a SEM observation image of Comparative Example 11. In addition, in this test example, an inorganic powder having a larger particle size than that of Test Examples I and II was used, and therefore the dispersion index was determined based on the following index.
[0161] ×: α less than 83%
[0162] ○: α is 83% or more
[0163] [Table 3]
[0164] Table 3
[0165]
[0166] As shown in Table 3, it was confirmed that in Examples 5 to 8 in which (A) the size and content ratio of the conductive powder, (B) the size and content ratio of the dielectric powder, and (C) the formulation of the binder resin were different, both the homogeneity of the coating film and the gravure printability could be achieved.
[0167] <Test Example IV>
[0168] In this test example, the (D) solvent was further studied. As the (D) solvent, in addition to the hydrocarbon solvent (cycloalkane solvent), the first solvent and the second solvent shown in Table 4 were prepared as solvents other than the hydrocarbon solvent, and they were mixed in the blending ratio shown in Table 4. Except for this, the same operation as in Example 5 was performed to prepare conductive pastes (Examples 9 to 24). Then, the drying property and sheet corrosion resistance were evaluated. It should be noted that the total SP value δ of the first solvent and the second solvent in Table 4 is all Calculate according to the following formula.
[0169] δ all =(SP value of the first solvent×content ratio of the first solvent (%)+SP value of the second solvent×content ratio of the second solvent (%) / (content ratio of the first solvent (%)+content ratio of the second solvent (%)).
[0170] [Evaluation of drying properties]
[0171] The conductive paste was analyzed by differential thermal analysis (TG-DTA). The measurement conditions were as follows.
[0172] Sample size: Conductive paste 5 mg
[0173] Gas flow rate: Air: 200ml / min
[0174] Program: Rise from room temperature to 85°C at 20°C / min, then maintain at 85°C
[0175] As an example, Figure 7 The TG-DTA measurement graphs of Examples 13, 19, and 9 are shown in the figure. Then, based on the measurement graph, the time when the weight change disappears (the weight change rate is 0.1 mass % or less) is calculated as the drying time. The results are shown in the "Drying Time" column of Table 4. Then, the drying properties of the conductive paste of each example were evaluated based on the following indicators. The results are shown in the "Judgment Result-Drying Property" column of Table 1.
[0176] △: Drying time is less than 15 minutes or more than 25 minutes
[0177] ○: Drying time is 15 minutes or more and 25 minutes or less
[0178] [Evaluation of sheet corrosion properties]
[0179] In the same manner as in Test Example 1, the conductive paste of each example was gravure printed on a dielectric green sheet containing barium titanate, and dried at 80° C. for about 5 minutes to form a coating film. Then, the coating film was observed by SEM from the dielectric green sheet side to obtain a SEM observation image. It should be noted that the acceleration voltage was set to 20 kV and the observation magnification was set to 1000 times. Figure 8 This is an example of a SEM observation image. Figure 8 (A) is the SEM observation image of Example 19, Figure 8 (B) is the SEM observation image of Example 16. Figure 8 (C) is the SEM observation image of Example 9. Next, the area of the black portion (resin pool portion) was compared based on the SEM observation image. Then, the sheet erosion resistance was evaluated based on the following indexes. The results are shown in the "Judgment Result-Sheet Erosion Resistance" column of Table 1.
[0180] △: The area of the black part is 20% or more
[0181] ○: The area of the black portion is 5% or more and less than 20%
[0182] ◎: The black area is less than 5%
[0183] [Comprehensive judgment]
[0184] In addition, a comprehensive evaluation was performed based on the above-mentioned drying evaluation results and sheet erosion evaluation results. For the comprehensive evaluation, "◎" was recorded as 2 points, "○" was recorded as 1 point, and "△" was recorded as 0 points. The total score of 0 points was recorded as "△", 1 point was recorded as "○", 2 points were recorded as "○", and 3 points were recorded as "◎". The results are shown in the "Judgment-Comprehensive" column of Table 4.
[0185] [Table 4]
[0186] Table 4
[0187]
[0188] As shown in Table 4, in Examples 12 and 13 using dodecyl alcohol ester or decanol as the second solvent, the drying properties and sheet erosion properties were relatively poor compared to the other examples. In contrast, by making the (D) solvent contain a solvent having a boiling point of 230°C or less and an SP value of 9.9 (cal / cm 3 ) 0.5 The following solvents as the second solvent can improve at least one of the drying property and the sheet erosion property compared with Examples 12 and 13. As shown in Examples 17 to 24, by using a combination of solvents having a boiling point of 200°C or higher and an SP value of 10.0 (cal / cm 3 ) 0.5The first solvent has a boiling point of 220°C or less and an SP value of 9.5 (cal / cm 3 ) 0.5 The following second solvent can further enhance the sheet corrosiveness.
[0189] <Test Example V>
[0190] In this test example, the binder resin (C) was further studied. As the binder resin (C), two types of polyvinyl butyral (S-LEC (registered trademark) of Sekisui Chemical Co., Ltd.) with different weight average molecular weights shown in Table 5 were used. Other than that, the same operation as in Example 2 was carried out to prepare conductive pastes (Examples 25 and 26), and the evaluation was carried out in the same manner as in Test Example 1. The results are shown in Table 5.
[0191] [Table 5]
[0192] Table 5
[0193]
[0194] As shown in Table 5, it was confirmed that, similar to Example 2, Examples 25 and 26 in which the weight average molecular weight of (C2) PVB was 100,000 to 200,000 could also achieve both the homogeneity of the coating film and the gravure printability.
[0195] The above describes suitable embodiments of the present invention. However, the above embodiments are merely illustrative, and the present invention can be implemented in various other ways. The present invention can be implemented based on the contents disclosed in this specification and the technical common sense in the field. The technology described in the claims includes various deformations and changes to the embodiments illustrated above. For example, part of the above embodiments can be combined or replaced with other deformation modes. In addition, as long as the technical features are not described as necessary, they can be deleted as appropriate.
[0196] Description of Reference Numerals
[0197] 1 Multilayer Ceramic Capacitors (MLCC)
[0198] 10 Stacked Chips
[0199] 10a Unfired laminate
[0200] 20 Dielectric layer
[0201] 20a Dielectric green sheet
[0202] 30 Internal electrode layer
[0203] 30a coating
[0204] 40 External electrodes
Claims
1. A conductive paste for gravure printing, comprising: (A) conductive powder, (B) dielectric powder, (C) binder resin, (D) solvent and (E) dispersant, The (E) dispersant is a compound represented by the following formula (2): in, A in formula (2) 1 , A 2 are each independently hydrogen, an alkali metal or an alkaline earth metal, R is a linear or branched, saturated or unsaturated aliphatic group having 4 to 30 carbon atoms, At 25°C, the conductive paste was heated at a shear rate of 40 s. -1 Viscosity V 40 Less than 5Pa·s.
2. The conductive paste according to claim 1, wherein The conductive paste is heated at a shear rate of 4 s -1 The viscosity V4 is relative to the viscosity V 40 The ratio (V4 / V 40 ) is less than 7.
3. The conductive paste according to claim 1 or 2, wherein The ratio (D1 / D2) of the average particle size D1 of the (A) conductive powder to the average particle size D2 of the (B) dielectric powder is 2 or more.
4. The conductive paste according to claim 1 or 2, wherein The (D) solvent includes a hydrocarbon solvent and a solvent other than a hydrocarbon solvent. The solvent other than hydrocarbons includes a solvent having a boiling point of 230°C or less and a Fedors solubility parameter of 9.9 (cal / cm 3 ) 0.5 The following solvents.
5. The conductive paste according to claim 4, wherein The solvent other than hydrocarbons comprises: The boiling point is above 200°C and the solubility parameter is 10.0 (cal / cm 3 ) 0.5 The first solvent above; as well as The boiling point is below 220°C and the solubility parameter is 9.5 (cal / cm 3 ) 0.5 The following second solvent.
6. The conductive paste according to claim 4, wherein The solubility parameter of the solvents other than hydrocarbons is 9.8 (cal / cm 3 ) 0.5 the following.
7. The conductive paste according to claim 1 or 2, wherein When the entire conductive paste is taken as 100 mass %, the (E) dispersant is 0.5 mass % or less.
8. The conductive paste according to claim 1 or 2, wherein The (C) binder resin comprises a polyvinyl acetal resin, The weight average molecular weight of the polyvinyl acetal resin is 200,000 or less. 9 . The conductive paste according to claim 1 , which is used for forming an internal electrode layer of a multilayer ceramic electronic component. 10 . A method for producing an electronic component, comprising applying the conductive paste according to claim 1 to a substrate and firing the paste.
Citation Information
Patent Citations
Conductive paste for photogravure used for multilayer ceramic capacitor internal electrode
JP2012174797A
Nickel ultrafine powder, conductive paste and method of producing nickel ultrafine powder
JP2014122368A
Dispersibility evaluation method, dispersibility evaluation device, and computer readable recording medium having program to cause computer to achieve dispersibility evaluation function recorded therein
JP2015007542A
Measuring method and processing method of bonded substrate and device used for the same
JP2019174262A
Low-temperature sintering conductive paste, conductive film using same, and method for forming conductive film
CN103180913A
